Analysis of Stress Concentration Factor for Tensile Characteristics of Syntactic Foam Using Finite Element Method - Salleh, Zulzamri; Islam, Md Mainul; Epaarachchi, Jayantha Ananda (Journal of Research Updates in Polymer Science, 2017)
This paper presented the stress concentration factor (SCF) around the half circular edge of tensile specimens made of syntactic foam using finite element software Strand7 software. The study is a preliminary effort, which investigates the effect of variations of crack geometry on the stress concentration factor on a tensile specimen subjected to a constant, uniform, uniaxial tensile load. The material property is graded for varying Young’s Modulus and Poisson’s Ratio with different composition of glass microballoons. Finally, a uniform pressure is applied at the top and the model is constrained with symmetric boundary conditions at the left and bottom. As the result, these numerical results for both SCF experimental and simulation model are compared to those obtained from analytic fracture mechanics procedures and are found to be varied. In addition, the SCF is sensitive to the modulus of elasticity, particularly for lower composition weight percentage (wt.%), while it is also varied with the different weight percentage (wt.%) of glass microballoons, which is led by 2 wt.% specimen.